Fibroblast growth factor 8: Multifaceted role in development and developmental disorder - Huamin Yin; Lian Duan; Zhendong Wang; Li Liu; Jingling Shen (Genes and Diseases)
Fibroblast growth factor 8 (FGF8), a secreted signaling molecule, involves in regulating cell survival, proliferation, migration, and differentiation. It exhibits a highly dynamic gene expression pattern throughout embryonic development, participates in craniofacial structures, limbs, internal organs, brain development, and is crucial during organogenesis. The dysregulation of precise localization and dosage of FGF8 at distinct embryonic stages can lead to developmental multiorgan abnormalities. This comprehensive review explores the FGF8 expression in humans and mice, summarizes the involvement of FGF8 in various tissues including craniofacial, limbs, cardiovascular and urogenital system, nephrogenesis, lung, and brain development as well as developmental abnormalities resulting from the aberrant regulations of FGF8 such as skeletal abnormalities, ciliopathies, and holoprosencephaly.